2017
DOI: 10.1186/s12889-017-4765-y
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in health system input between minority and non-minority counties and their effects on maternal mortality in Sichuan province of western China

Abstract: BackgroundThe maternal mortality rate (MMR) markedly decreased in China, but there has been a significant imbalance among different geographic regions (east, central and west regions), and the mortality in the western region remains high. This study aims to examine how much disparity in the health system and MMR between ethnic minority and non-minority counties exists in Sichuan province of western China and measures conceivable commitments of the health system determinants of the disparity in MMR.MethodsThe M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Guo and Huang 2019 [8] note the challenge of looking at county level data due to the instability of birth rates considering the small size of county populations; qualitative data can be helpful to understand and assess factors rather than relying on quantitative data which may not be reliable. Our quantitative data showed that maternal deaths are disproportionately likely to be Yi ethnic minority women, confirming prior research that shows minority-prevalent counties have higher MMR than nonminority prevalent counties [32] and the need for further rsearch to understand this discrepancy [33].…”
Section: Discussionsupporting
confidence: 84%
“…Guo and Huang 2019 [8] note the challenge of looking at county level data due to the instability of birth rates considering the small size of county populations; qualitative data can be helpful to understand and assess factors rather than relying on quantitative data which may not be reliable. Our quantitative data showed that maternal deaths are disproportionately likely to be Yi ethnic minority women, confirming prior research that shows minority-prevalent counties have higher MMR than nonminority prevalent counties [32] and the need for further rsearch to understand this discrepancy [33].…”
Section: Discussionsupporting
confidence: 84%
“…Sichuan Province consists of 67 minority counties and 116 nonminority counties [17]. Data for this study were obtained from the population-based Direct Report System of Maternal and Child Health(DRSMCH)in Sichuan.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Although the proportion of children treated in provincial/municipal hospitals has increased (p<0.001), it only increased by 13.6% in the minority counties in 2017 ( Figure 3). The decline of PU5MR was due to social and economic growth, an increase in health and human resources, the improvement of child nutrition, and an increase access to child healthcare [17,18].…”
Section: Ethnic Disparity In Pu5mrmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Sichuan is important for China. Ren found that health human resources explained part of the difference in maternal mortality rate between minority and non-minority counties in Sichuan [19]. Sichuan province has issued a series of policies and measures to strengthen the construction of health human resources team, such as increasing investment in health human resources, strengthening education and training, and promoting various talent projects, which had achieved effective results.…”
Section: Introductionmentioning
confidence: 99%